(untitled) (Colombia Medica, 2008)
Introduction: A predominant molecular component analyzed in the study of neurodegenerative diseases is the presence of the Tau-GSK3β complex and its association with protein aggregation into the cell. Several evidences show that GSK3β has an important role in abnormal pattern of the phosphorylation of Tau. However, the molecular events that are governing this complex are unknown. Aim: To determine the effect of 17 β-estradiol treatment on the expression and association of Tau hyperphosphorylation responsible kinases. Methods: 17 β-estradiol treatments were realized in the hippocampus of ovariectomized adult wistar rats and in hippocampal primary cultures treated with β-amiloid. Protein complex association was assessed by co-immunoprecipitation, toxicity assay by LDH release and cell morphologic changes by confocal microscopy. Results: Our results show that 17β-estradiol produced dissociation of macromolecular complexes like Tau/GSK3β, Tau /GluR2/3, Tau/FAK, and Tau/Fyn in hippocampus of adult rat. In addition the expression of GSK3β-ptyr was decreased by the hormonal treatment and this one regulated the defosforilation of Tau in an excitotoxicity model by β-amiloid. Conclusions: It suggests new targets that will contribute to neuroprotection and neuronal plasticity studies mediated by the estrogen.